Exploring English lecturers self-efficacy in the use of educational technology in post COVID-19 pandemic - Eva Nikmatul Rabbianty; Diana Nur Utami; Mega Fariziah Nur Humairoh; Nunung Suryati (Universitas Syiah Kuala, 2024)
This study examines the levels of self-efficacy and factors influencing the self-efficacy on the use of educational technology among English lecturers in Islamic higher education institutions in East Java, Indonesia, in the post-COVID-19 pandemic. There are two research questions addressed: 1) What levels of self-efficacy do the lecturers exhibit on the pedagogical skills and actual use of educational technology in the postCOVID19 pandemic? 2) What factors influence the lecturers self-efficacy on the use of educational technology in the postCOVID19 pandemic? Utilizing a survey research design, data were collected using an adapted version of the Professional Self-Efficacy Scale for Information and Communication Technology Teachers (PSES) questionnaire. The data from 37 participants were then analyzed using descriptive statistics. The result showed that the lecturers self-efficacy in their pedagogical skills and the actual use of educational technology was moderate, and they will continue integrating educational technology in their classrooms in the postCOVID19 era. Moreover, the qualitative data indicated that the lecturers had moderate skills in using technology with limited educational technology tools. Age, gender, qualifications, and teaching experience emerged as factors influencing the lecturers self-efficacy on the use of educational technology in classrooms. The findings highlighted the need for English lecturers in Islamic higher education institutions to broaden their skills in using educational technology for learning. Policymakers need to design appropriate strategies to enhance lecturers pedagogical practices in using educational technology for online learning to ensure effective and efficient teaching in the post-COVID-19 pandemic.